Geography-Driven Evolution of Potato Virus A Revealed by Genetic Diversity Analysis of the Complete Genome - Zhang, Wei; Sun, Xuhong; Wei, Xuyan; Gao, Yanling; Song, Jiling; Bai, Yanju (Frontiers in Microbiology, 2021)
Potato virus A (PVA), a member of the genus Potyvirus, is an important potato pathogen that causes 30%-40% yield reduction to global potato production. Knowledge on the genetic structure and the evolutionary forces shaping the structure of this pathogen is limited but vital in developing effective management strategies. In this study, we investigated the population structure and molecular evolution of PVA by analyzing novel complete genomic sequences from Chinese isolates combined with available sequences from Europe, South America, Oceania, and North America. High nucleotide diversity was discovered among the populations studied. Pairwise FST values between geographical populations of PVA ranged from 0.22 to 0.46, indicating a significant spatial structure for this pathogen. Although purifying selection was detected at the majority of polymorphic sites, significant positive selection was identified in the P1, NIa, and NIb proteins, pointing to adaptive evolution of PVA. Further phylogeny–trait association analysis showed that the clustering of PVA isolates was significantly correlated with geographic regions, suggesting that geography-driven adaptation may be an important determinant of PVA diversification.